Investigating Students’ Attitudes Toward Learning based on Metaverse - Nawaiseh , Sabah Jamil Al-; Ahmad , Fadi Bani; Nawaiseh , Asmaa Jameel Al-; Nawaiseh, Ammar M. Al- (International Journal of Membrane Science and Technology, 2023)
By merging augmented Reality (AR) and Virtual Reality (VR), the real world becomes a metaverse. This study aims to determine students’ attitudes toward learning based on a metaverse platform depending on different variables. The researchers applied a Quasi-experimental method of one group post-test design to a random sample of 100 students from the Faculty of Information Technology, Mutah University. The system of the human body was selected and three topics were introduced: the circulatory system, the nervous system, and the digestive system. A scale was developed to measure the students' attitudes after watching the lessons prepared by the proposed AR platform and then to analyze their feedback from the answers collected in a well-prepared questionnaire. The results showed that there is a statistically significant difference in students’ attitudes toward learning based on the metaverse. Furthermore, the study recommends adopting the use of the metaverse platform in learning and promoting research in the areas of AR and metaverse